Amorpheus: a Python-based software for the treatment of X-ray scattering data of amorphous and liquid systems. Issue 1 (2nd January 2022) - Boccato, S.; Garino, Y.; Morard, G.; Zhao, B.; Xu, F.; Sanloup, C.; King, A.; Guignot, N.; Clark, A.; Garbarino, G.; Morand, M.; Antonangeli, D.
ABSTRACT: The diffuse scattering signal of amorphous or liquid systems contains information on the local atomic structure, and this can be related to the density, compressibility, thermal expansion and other thermoelastic properties. However, the analysis and full exploitation of the diffuse scattering signal, in particular for systems under extreme conditions of high pressures and temperatures are difficult to handle. Amorpheus is a Python-based software allowing the determination of the structure factor and the radial distribution function of amorphous and liquid systems. Based on previously reported methodologies, Amorpheus stands out for the implementation of automatic algorithms allowing the user to choose the most suitable parameters for the data treatment and making possible systematic analysis of datasets collected in experiments carried out in Paris-Edinburgh press, multi-anvil apparatus or diamond anvil cell.